2004
DOI: 10.1210/jc.2003-031786
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Leydig Cell Function in Infertile Men: A Study of 357 Idiopathic Infertile Men and 318 Proven Fertile Controls

Abstract: To investigate whether an impaired Leydig cell function is present in severely oligospermic men, serum testosterone (T), LH, estradiol (E(2)), and SHBG levels in 357 idiopathic infertile men were compared with levels in 318 proven fertile men. In addition, the T/LH ratio, E(2)/T ratio, and calculated free T index (cFT) were compared between the two groups.A shift toward lower serum T levels, cFT, and T/LH ratio and higher serum LH, E(2), and E(2)/T levels was observed in the group of infertile men. On average,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
148
3
11

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(186 citation statements)
references
References 37 publications
24
148
3
11
Order By: Relevance
“…This data fits with growing evidence that subtle deficiency in fetal androgens is a major determinant of adult male reproductive disorders, such as low sperm production (16,17), and might explain why low sperm counts are often associated with compensated Leydig cell failure in men (18). However, the mechanisms through which fetal events could influence adult testosterone levels are unknown.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…This data fits with growing evidence that subtle deficiency in fetal androgens is a major determinant of adult male reproductive disorders, such as low sperm production (16,17), and might explain why low sperm counts are often associated with compensated Leydig cell failure in men (18). However, the mechanisms through which fetal events could influence adult testosterone levels are unknown.…”
supporting
confidence: 87%
“…There is a similar connection between reduced fetal androgens and reduced adult sperm counts/sperm production in men and rats (15,16). What further ties these observations together is that men with low sperm counts commonly exhibit compensated adult Leydig cell failure, although why is unknown (18,60,67). It has been suggested that it may be indicative of a common underlying (fetal) cause (18), and our present animal experimental studies provide direct supporting evidence for this suggestion.…”
Section: -Hsd3supporting
confidence: 77%
“…Both parameters were assessed only for single time points per day (from 9:00 a.m. to 11:00 a.m.), and therefore being pulsatile hormones, such measures are of statistical value only for the sample population, where the T/LH ratio should reflect the average capacity of Leydig cells for steroidogenesis. 24,25 Although on PND24 at the beginning of puberty, there appeared to be a trend for both DES and DBP groups to have lower individual T/LH ratios compared to controls (data not shown), this did not reach statistical significance (P50.2), and was definitely not maintained at the later time point (PND90).…”
Section: Discussionmentioning
confidence: 93%
“…The ratio of T to LH within individuals has been interpreted as a measure of total Leydig cell functional capacity. 24,25 Although there was a major increase in this parameter (mean6s.e.m. for all groups combined; P,0.001) between PND24 (0.03760.031; n518) and PND90 (0.44360.482; n518), as the Leydig cells differentiate and the HPG axis attains its final mature status (Figure 3e), there were no differences between treatment groups at all time points.…”
Section: Effect Of Maternal Dbp and Des Treatments On Testis Parametersmentioning
confidence: 90%
“…This premise is based on the findings of previous studies, which showed that men with idiopathic infertility had significantly lower concentrations of serum testosterone, higher LH, higher estrogen, lower testosterone-to-LH ratios and higher estrogen-to-testosterone ratios than men with proven fertility [9]. Similarly, men with non-obstructive azoospermia or severe oligozoospermia were reported to have significantly lower concentrations of serum testosterone, higher estradiol, lower serum testosterone-to-estradiol ratios, and higher FSH than age-matched fertile controls [10].…”
Section: Discussionmentioning
confidence: 99%